Ethnic identity, procedural justice, and offending: does procedural justice work the same for everyone? - McLean, Kyle (Crime & delinquency, 2017)
Identity judgments are central to the theoretical arguments of procedural justice theory. Perceptions of procedural injustice have been argued to compromise an individual’s social identity and contribute to disengagement from group values and norms. Thus, it is important to clarify the relationship between perceptions of procedural justice and specific facets of social identities, such as ethnic identity. This study attempts to evaluate the relationship between these concepts by examining the potential interaction effect between procedural justice and ethnic identity on two measures of offending, self-report and number of arrests, in a longitudinal study of serious juvenile delinquents.